ANALISIS PENGARUH CURRENT RATIO, PRICE TO EARNING, DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA - Anisyah, Yuniar; Supriyadi, Stevanus Gatot (Jurnal MBE Manajemen Bisnis, Equilibrium, 2024)
This research aims to determine the fundamental factors regarding the share prices of companies whose consistency is listed on the LQ45 Index during the 2019-2022 certain periods, either partially or simultaneously. The sample in this research was 22 LQ45 companies. The sample criteria used in this research are that the company has been continuously included in the LQ45 index for the last 3 years (2019-2022) and has the necessary data regarding the current ratio, price to income and return on equity. This research is quantitative research, using secondary data. The data analysis used is simple linear regression analysis consisting of a determination test and a t test with the help of the IBM SPSS 24 7z program with purposive sampling. The results of this partial research show that CR and PER have no effect on share prices, while ROE has a positive effect on share prices in LQ45 Index companies in the 2019-2022 period. Simultaneous or joint testing shows that all variables have an influence on share prices by 42.9%.The results of this research are used as knowledge for investors regarding good company financial performance for making investor decisions.